2013
DOI: 10.1186/1471-244x-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing comorbidity in psychiatric hospital: challenging the validity of administrative registers

Abstract: BackgroundThis study will explore the validity of psychiatric diagnoses in administrative registers with special emphasis on comorbid anxiety and substance use disorders.MethodsAll new patients admitted to psychiatric hospital in northern Norway during one year were asked to participate. Of 477 patients found eligible, 272 gave their informed consent. 250 patients (52%) with hospital diagnoses comprised the study sample. Expert diagnoses were given on the basis of a structured diagnostic interview (M.I.N.I.PLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 43 publications
1
56
0
1
Order By: Relevance
“…Multiple studies reported changes in brain structure (77) and function (82)(83)(84) following chronic antidepressant treatment. If such effects are present in neuroimagingbased classification experiments, the brain patterns identified might be associated with drugeffects rather than with effects specific to the pathology of depression.…”
Section: Limitations Of the Current Meta-analysis: Effect Of Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies reported changes in brain structure (77) and function (82)(83)(84) following chronic antidepressant treatment. If such effects are present in neuroimagingbased classification experiments, the brain patterns identified might be associated with drugeffects rather than with effects specific to the pathology of depression.…”
Section: Limitations Of the Current Meta-analysis: Effect Of Clinicalmentioning
confidence: 99%
“…For example, the recent investigation of the test-retest reliability of the diagnostic categories of the DSM V, indicated that MDD was diagnosed with limited accuracy (81). Similarly, MDD and bipolar disorder might frequently be confused (82). In effect, misclassification in the initial psychiatric assessment might have contributed to reductions in classification performance.…”
Section: Future Challenges For Neuroimaging-based Classification Of Dmentioning
confidence: 99%
“…Diagnoses of psychotic disorders in the NPR also have not yet been subjected to formal validity testing, but a recent report comparing clinical and research-based diagnostic evaluations demonstrated good agreement for schizophrenia. 51 Costs of medications are limited to antipsychotics as reliable data on other medications were not available. We could not access reliable data regarding the criminal justice system costs associated with schizophrenia.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The ability to use a telephone is considered one of the instrumental activities of daily living, and mobile phones are rapidly replacing land-line telephones as an “everyday technology”(Czaja et al, 2006). Furthermore, a number of interventions focusing on schizophrenia have used mobile phone to extend psychosocial interventions to the community, delivered through either live communication with a provider, text messages, or smartphone applications, with intervention foci reminders or prompts to engage in self-management activities outside of the clinic setting (Depp et al, 2010; Palmier-Claus et al, 2013) or elements of evidence-based treatments such as cognitive behavioral therapy for SMI (Ben-Zeev et al, 2014; Granholm, Ben-Zeev, Link, Bradshaw, & Holden, 2012). Thus, mobile phone use can be viewed as an increasingly relevant indicator of functional status and as a potential conduit to intervention in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%